Evaluation of susceptibility to mass movements from morphometric variables at the interface between the southern plateau and the central depression of the Vale do Taquari region – Rio Grande do Sul - Souza, Tainara Godoy de (2021)
The occurrence of disasters in Brazil by natural processes has been increasing along the years. One of these phenomena is mass movements, a destructive phenomenon which may cause damage to socioeconomic. The morphometric variables are becoming useful in geomorphologic analysis, mainly in diagnosis of susceptible areas to those processes. This way, the objective of this work is to identify susceptible areas of mass movements in the interface between meridional plateau and the central depression in Vale do Taquari region, using geomorphometric variable at a scale of 1:250.000. This morphometric analysis contains Remote Sensing and geoprocessing, so it becomes an effective and low cost method. GIS software (Geographic Information System) was used to maps algebra from the statistical methods AHP (Analytical Hierarchy Process) and Delphi, in which pondering and the hierarchy of influential variables in this analysis. The final product is an analysis map of susceptibility to mass movements in the mentioned region. In the map it is observed that the region has a high degree of susceptibility in most aspects. With this data it is possible to carry out a proper planning and management of the territory, providing more safety to the occupation of those areas.